Палеозоологические исследования в Сумской области (исторический аспект) - Ковальчук, А.Н. (Вестник зоологии, 2012)
Обобщены итоги палеозоологических исследований, проводившиеся на территории Сумской обл. с конца XVIII до XXI вв. Установлено качественное и количественное соотношение палеонтологического материала, обнаруженного на протяжении указанного периода. Подчеркнута важность проведения региональных палеонтологических работ и их перспективность на территории Сумской обл. Attempt of generalization of the results of paleozoological researches, which were spent in the territory of the Sumy region from the end of XVIII till XXI century, has been made in the article. Question about qualitative and quantitative parity of the paleontologic material, which was found throughout the specified period, was solved. The considerable attention was given to the contribution of teachers and students of the Sumy State Pedagogical University named after A. S. Makarenko in the development of the above-stated researches. Importance of the regional paleontologic works and their perspectivity in the territory of the Sumy region was underlined.